Students´ Self-Image Construction Through Writing from a Social - Siachoque Cárdenas, Nayibe Pilar (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This qualitative case study discusses the main factors that influence self-image construction of eighth graders, through the implementation of writing tasks. Two theoretical constructs grounded this study: adolescence, and identity which breaks down into: self-image and self-esteem. This study delves into how students construct their self-image and the aspects of behavior that shape it. The study wasconducted with 34 students in a public school in Boyacá. Moreover, the instruments used to gather data were students´ artifacts, a semi-structured interview and a questionnaire. It was found that there is a dichotomy in the participants’ behavior while they are at home with their parents and when interacting with peers at school. It was also found that the behaviors that shape their self-image relate to the  way they are transitioning from children to adolescents. Students started defining themselves with more critical and mature insights.